The development of a nurse-led preoperative anaesthesia screening tool by Delphi consensus - Nejthardt, M B; Alexandris, P; Bechan, S; Bijli, M F A; Chetty, S; Dippenaar, J M; Gibbs, M W; Johnson, M; Kluyts, H; Llewellyn, R; Motiang, M; Mogane, P; et al. (South African medical journal, 2024)
Background Low- and middle-income countries have a critical shortage of specialist anaesthetists. Most patients arriving for surgery are of low perioperative risk. Without immediate access to preoperative specialist care, an appropriate interim strategy may be to ensure that only high-risk patients are seen preoperatively by a specialist. Matching human resources to the burden of disease with a nurse-administered pre-operative screening tool to identify high-risk patients who might benefit from specialist review prior to the day of surgery may be an effective strategy. Objective To develop a nurse-administered preoperative anaesthesia screening tool to identify patients who would most likely benefit from a specialist review before the day of surgery, and those patients who could safely be seen by the anaesthetist on the day of surgery. This would ensure adequate time for optimisation of high-risk patients preoperatively and limit avoidable day-of-surgery cancellations. Methods A systematic review was conducted to identify preoperative screening questions for use in a three-round Delphi consensus process. A panel of 16 experienced full-time clinical anaesthetists representing all university-affiliated anaesthesia departments in South Africa participated to define a nurses’ screening tool for preoperative assessment. Results Ninety-eight studies were identified, which generated 79 questions. An additional 14 items identified by the facilitators were added to create a list of 93 questions for the first round. The final screening tool consisted of 81 questions, of which 37 were deemed critical to identify patients who should be seen by a specialist prior to the day of surgery. Conclusion A structured nurse-administered preoperative screening tool is proposed to identify high-risk patients who are likely to benefit from a timely preoperative specialist anaesthetist review to avoid cancellation on the day of surgery.